1965
DOI: 10.1111/j.1476-5381.1965.tb01790.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Isometamidium: The Effect of Isometamidium, Homidium and Pyrithidium on the Infectivity of Trypanosomas for Mice

Abstract: During the course of an investigation into the antitrypanosomal activity of isometamidium, some phenanthridinium compounds were administered to mice infected with Trypanosoma rhodesiense or T. congolense; trypanosomes from these mice were subinoculated into fresh mice at various times after treatment, and the effect of the compounds on infectivity was noted. In vivo/in vivo experiments of this kind have been carried out in the past by Lock (1950) with dimidium bromide and T. congolense and by Ormerod (1951) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1968
1968
1988
1988

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The highest levels of ethidium detected in blood and tissue fluid (120-180 ng/ml) following i.m. injection of the recommended curative dose (1 mg/kg) are maintained for a short period and are approximately 2 orders of magnitude less than trypanocidal levels observed in the in vitro studies of Newton (1957) and Hill (1965). Newton showed the growth inhibitory concentration of ethidium for trypanosomatid flagellates cultured in vitro to be 10-20 fig/ml and Hill showed that the ethidium concentration needed to render T. congolense uninfective to mice was 10 /ig/val for 6 h. The maximum blood concentration detected in the current work is much closer to the value of 312 ng/ml required to inhibit the motility of T. brucei in vitro.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The highest levels of ethidium detected in blood and tissue fluid (120-180 ng/ml) following i.m. injection of the recommended curative dose (1 mg/kg) are maintained for a short period and are approximately 2 orders of magnitude less than trypanocidal levels observed in the in vitro studies of Newton (1957) and Hill (1965). Newton showed the growth inhibitory concentration of ethidium for trypanosomatid flagellates cultured in vitro to be 10-20 fig/ml and Hill showed that the ethidium concentration needed to render T. congolense uninfective to mice was 10 /ig/val for 6 h. The maximum blood concentration detected in the current work is much closer to the value of 312 ng/ml required to inhibit the motility of T. brucei in vitro.…”
Section: Discussionmentioning
confidence: 91%
“…Many instances of ethidiumresistant trypanosome strains have been reported (for example, Williamson, 1970;MacLennan & Na'lsa, 1970;Gray & Roberts, 1971) but the failure of ethidium to cure T. congolense or T. brucei infections in rabbits under the experimental conditions reported in this paper was not due to drug resistance, and extrapolation from the ethidium levels found to be trypanocidal in vitro may be misleading. The work of Newton (1957), Hill (1965) and Goodwin & Tierney (1977) all used constant ethidium concentrations in vitro. While the maximum blood ethidium concentrations present in infected rabbits are clearly sufficient to kill many of the trypanosomes present, it is equally clear that some survive.…”
Section: Discussionmentioning
confidence: 99%
“…rhodesiense at concentrations of up to 0.1 mg/ml, probably due to the in vitro system used. Hill (1965) found that the drug was active against T. congoleme in vitro but the activity was less than that observed in vivo. This may be attributed to variations in the parasite metabohn under in vztro and in vivo conditions.…”
Section: In Vitro Culture Studiesmentioning
confidence: 93%